MEDIATION AND MODERATION ANALYSIS USING MULTI-GROUP PLS-SEM: DETERMINANTS OF PATIENT LOYALTY IN HOSPITALS - Hermanto Hermanto; Haris Maupa; Indra Widjaja (International Journal of Application on Economics and Business, 2026)
Hospitals in Indonesia are currently challenged to maintain patient loyalty amid intensified competition and changing healthcare expectations. Being recognized as the preferred provider among patients depends largely on two strategic factors: a favorable hospital image and a trusted reputation. This study explores how both variables shape patient loyalty, directly and indirectly, through the mechanism of perceived value. Patient satisfaction and service quality are further examined as determinants of perceived value, which links these constructs to hospital image, reputation, and loyalty outcomes. Using data from 450 respondents, analysis was conducted with Structural Equation Modeling (SEM) in SmartPLS 4.0. The model achieved strong explanatory capacity, with R² values of 0.67 for hospital image, 0.68 for reputation, and 0.72 for both perceived value and loyalty. Empirical results indicate that eight out of ten hypotheses were statistically supported, confirming that satisfaction, service quality, and perceived value play vital roles in reinforcing hospital image, reputation, and loyalty. Subgroup analysis by age revealed that these associations were generally stable, except for a slight variation among respondents aged 41–50. To remain the provider of choice, hospitals should focus on strategic branding, continuous service innovation, modernization of facilities, and the professional competence of medical staff. Strengthening communication and quality improvement initiatives based on patients’ perceived values will further enhance satisfaction and sustain long-term loyalty.